Ground penetrating radar - Daniels, D. J. (Institution of Engineering and Technology, 2004)
The new edition of Ground Penetrating Radar is a greatly expanded treatment of a radar technique that penetrates the surface of the ground or man-made structures and contains many additional contributions by leading experts in the field. Ground penetrating radar is increasingly used to examine archaeological sites, engineering structures, (e.g. bridges, roads) etc., and has come to some prominence in forensic investigations. GPR is also used for the detection of landmines.